The management of the archaeological heritage of the Pontifical catholic university of peru - Bringas Heredia, Andrea (2019)
The archaeological sites located inside the campus of the Pontifical Catholic University of Peru (PUCP) are part of an extensive pre-Hispanic complex that, unlike other sites that existed in Metropolitan Lima, managed to be partially conserved. It occurred mainly due to the work of people committed to heritage such as Dr. Josefina Ramos de Cox and other members of the Archeology Seminary of the university. The initial management actions taken towards this piece of heritage, consisting of Huaca 20, Huaca 64 and the Inca Trail, were related to defense, protection and research. On the other hand, recent actions have been associated to the rescue and enhancement of the monuments, tasks that have been carried out thanks to political will institutional commitment. The following article aims to present the experience of the management of the university’s archaeological heritage, which will be considered on the basis of normative frameworks, values ​​and functions. Likewise, it evaluates achievements linked to the exercise of the above-mentioned commitments, and proposes challenges related to the integration of archaeological heritage to the daily life of the PUCP community.